Koncept prilagajanja geokonstrukcij z upoštevanjem vplivov podnebnih sprememb - Bračko, Tamara (Urbani izziv, 2024)
This article addresses potentially unstable slope areas in the context of climate change. A possible approach to mitigating and adapting slopes is presented, considering various solutions primarily based on natural processes. The methodology incorporates planning considerations for the effects of climate change on the geomechanical properties of soils and consequently the response of soils and structures. The effects of selected measures to adapt to climate change are also demonstrated. A concept for adapting potentially unstable geotechnical structures is proposed, considering anticipated climate changes for geomechanical analyses and geotechnical planning, which encompasses the causal chain: climate change signals, effects, impacts (consequences), and measures. The implementation of the concept is illustrated through a typical slope stability analysis. The conclusion of the analysis highlights factors such as water net infiltration into the slope, soil permeability, and groundwater flow within the slope, which are often crucial for slope stability. These factors can also be regulated through nature-based solutions.
Keywords: climate change adaptation; infiltracija padavin; na naravi temelječe rešitve; nature-based solutions; neto infiltracija vode; prilagajanje podnebnim spremembam; rainfall infiltration; slope stability; stabilnost pobočij; water net infiltration